Peran Perencanaan Bisnis Produk Sereal Berbasis Sayur Untuk Mendukung Gaya Hidup Sehat - Maykhalis Nur Safitri; Devina Ananta Sari; Fitria Kartika Sari; Fazhabilla Nanda Savitri; Sonja Andarini; Indah Respati Kusumasari (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Many people in Indonesia do not eat enough vegetables. This is a problem for public health. This study made and reviewed a business plan for a vegetable cereal product. The goal is to give people a healthy, easy, and nutritious food choice. The method used was qualitative, with interviews, observations, and collecting documents. The study took place in Surabaya with people of different ages. The result showed that the cereal, made from carrots, spinach, and tomatoes, was liked by many because it tasted good and was healthy. The product was sold using social media and online shops, which helped grow the business. The financial study showed a return on investment of 179.57% in six months. The product also reached break even at 28 portions sold. This cereal has the chance to help people eat better and also support local farmers and small businesses. The vegetable cereal is a good business idea and helps people live a healthier life.